Possibility of Phytoxicity of Sewage Treatment Stations in the Germination of Lettuce Seed (Lactuca sativa) - Tavares, Rosangela Gomes; Sobrinho, Maurício A. da Motta; Arruda, Valmir Cristiano Marque de; Correa, Marcus Metri; Pereira, Luciana; Queiroz, Alessandro P. F. de (Revista Geama, 2018)
The final treatment and disposal of sludge generated at sewage treatment plants has become a crucial step in the waste management process. The present work carried out an evaluation of the sludge toxicity after dehydration and treatment with vermicomposting, through an ecotoxicity test using Lactuca sativa as bio-indicator. The percentage of relative germination and relative growth inhibition of the primary roots was determined for 5 dilutions obtained from the sludge sample. The results of the bioassay with lactuva sativa seed showed that the treatment with vermicomposting interfered in the germination rate, increasing the same the relative growth of the roots.  This way, corroborates not to indicate the disposal of this residue directly in the soil without any type of treatment.